2014
DOI: 10.1155/2014/680196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exogenous Lactase Administration on Hydrogen Breath Excretion and Intestinal Symptoms in Patients Presenting Lactose Malabsorption and Intolerance

Abstract: Objective. To establish whether supplementation with a standard oral dose of Beta-Galactosidase affects hydrogen breath excretion in patients presenting with lactose malabsorption. Methods. Ninety-six consecutive patients positive to H2 Lactose Breath Test were enrolled. Mean peak H2 levels, the time to reach the peak H2, the time to reach the cut-off value of 20 ppm, the cumulative breath H2 excretion, the areas under the curve, and a Visual Analogical 10-point Scale for symptoms were calculated. Genotyping o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The results were variable in 96 participants all of whom were genetically lactase deficient. About 22% became negative, in about 18% there was a significant reduction in tested breath hydrogen but in the rest there was no significant difference from baseline [191]. Reductions of symptoms did not follow reduction of hydrogen production suggesting symptomatic improvement may have been due to a placebo effect.…”
Section: Treatment Options For Lactose Intolerancementioning
confidence: 99%
“…The results were variable in 96 participants all of whom were genetically lactase deficient. About 22% became negative, in about 18% there was a significant reduction in tested breath hydrogen but in the rest there was no significant difference from baseline [191]. Reductions of symptoms did not follow reduction of hydrogen production suggesting symptomatic improvement may have been due to a placebo effect.…”
Section: Treatment Options For Lactose Intolerancementioning
confidence: 99%
“…Preliminary data showed an improvement of gastrointestinal symptoms and a decrease of H 2 levels at breath test with the administration of 1,500 U/day of β-galactosidase. However, more data regarding the efficacy of this microbial exogenous enzyme are needed [37]. Other evidence suggested that efficacy of exogenous lactase was obtained from Kluyveromyces lactis , Aspergillus oryzae , or Kluyveromyces lactis [38, 39].…”
Section: Management Of Lactose Intolerance and Nutritional Issuesmentioning
confidence: 99%
“…41 When evaluating the effectiveness of supplementation with this enzyme, some authors found a reduction of expired hydrogen and improvement of LI symptoms. 42,43 However, the supplement is not capable of fully hydrolyzing the lactose, with different results in each individual. 15 There are reports on the association of lactase supplements and allergic reactions and anaphylaxis.…”
Section: Enzyme Replacement Therapy With Exogenous Lactasementioning
confidence: 99%